Building block and rapid synthesis of catecholamines-inorganic nanoflowers with their peroxidase-mimicking and antimicrobial activities - Celik, Cagla (Sci Rep, 2020)
Protein incorporated flower-shaped hybrid nanostructures have received highly considerable attention due to their greatly enhanced catalytic activities and stabilities. Up to date, proteins, enzymes (mostly considered as proteins), and amino acids (as the building blocks of peptides and proteins) have been used as organic components of the hybrid nanoflowers. Herein, we present a rational strategy to rapidly form catecholamines (dopamine, epinephrine and norepinephrine)-copper ion (Cu(2+)) incorporated nanoflowers (cNFs) mostly in 3 hours and show their peroxidase-mimic catalytic, dye degradation and antimicrobial activities through Fenton-like reaction mechanism. We systematically studied effects of experimental parameters including catecholamine concentrations, reaction time and reaction pH values, on formation of the cNFs. We also explained that norepinephrine nanoflower (neNF) with its porous structure, high surface area, polar surface property behaves as an efficient Fenton agent by exhibiting highly much catalytic activities compared to dopamine nanoflower (dNF) and epinephrine nanoflower (epNF). We claim that the NFs formed using nonprotein molecules can be used in designing new generation nanobiocatalytics, antimicrobial agents, nanobiosensors and pharmaceutical products.